2015
DOI: 10.1186/s12955-015-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of posttraumatic stress disorder among survivors five years after the “Wenchuan” earthquake in China

Abstract: ObjectiveThe aim of this study was to investigate the prevalence of posttraumatic stress disorder (PTSD) and its risk factors among survivors in a heavily-hit area five years after the Wenchuan earthquake in 2008, China.Methods684 survivors from Beichuan county, the center of the Wenchuan Earthquake in 2008, were evaluated using the PTSD Checklist-Civilian Version (PCL-C) questionnaire in 2013.ResultsThe prevalence of PTSD among survivors was 9.2% in 2013. Significant risk factors of PTSD included gender (fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 23 publications
6
32
1
Order By: Relevance
“…A previous study of the Haiti earthquake also inveterate that being female as the risk factor for PTSD (Fawzi et al, 2009). This result was also steady with the previous earthquake surveys which found that being female as the predictor of PTSD (Kun et al, 2009;L.-P. Zhang et al, 2015). Gender differences in exposure to terror may be attributable to a number of factors; among these are women's higher senses of risk and poorer self-efficacy, as well as their inclination to use less useful coping strategies than men and tended to construe disasters more negatively (Solomon, Gelkopf, & Bleich, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…A previous study of the Haiti earthquake also inveterate that being female as the risk factor for PTSD (Fawzi et al, 2009). This result was also steady with the previous earthquake surveys which found that being female as the predictor of PTSD (Kun et al, 2009;L.-P. Zhang et al, 2015). Gender differences in exposure to terror may be attributable to a number of factors; among these are women's higher senses of risk and poorer self-efficacy, as well as their inclination to use less useful coping strategies than men and tended to construe disasters more negatively (Solomon, Gelkopf, & Bleich, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Psychological problems after a traumatic event can cause more damage than the impact of changes in material QoL [8]. Many disaster studies have found that physical injuries, work ability, financial problems, postdisaster mental illness and QoL are closely related [8,11,13]. A year after the disaster, we can not only still observe the effects of psychological problems but also see the increasing impact and inconvenience of serious physical injuries on financial problems.…”
Section: Resultsmentioning
confidence: 99%
“…HRQoL is determined in part by the patients' perceptions of their state of mental and physical health [9]. Many studies have shown that quality J Psychiatry, an open access journal ISSN: 2378-5756 of life (QoL) is significantly negatively correlated with age, female sex, mental illness, physical illness and economic problems and is positively correlated with social support and psychological assistance [10][11][12][13][14]. Therefore, a survey of post-disaster survivors' psychiatric diseases and QoL could be helpful for further mental rehabilitation preparation.…”
Section: Introductionmentioning
confidence: 99%
“…We excluded another 957 articles after reading the titles and abstracts, and retained the remaining 97 articles for further evaluation by reading the full texts. Finally, we selected 52 full-text articles on risk factors for earthquake-related PTSD among survivors for our meta-analysis ( Figure 1 ) [ 2 , 3 , 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 26 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Furthermore, 37 studies investigated the association bet...…”
Section: Resultsmentioning
confidence: 99%